Its about time we care about an equitable world: Women's unpaid care work and COVID-19 - Sarrasanti Ardinugroho, Nediana; Donkor, Felix Kwabena; Santos, Claudia; Tsagkari, Marula; Wannous, Chadia (IEEE Engineering Management Review, 2020)
Unpaid care work, mostly performed by women, is a central but undervalued contributor to economies. During the COVID-19 pandemic, the need for unpaid care work increased due to restricted movement, social isolation, and economic challenges. This pandemic has highlighted the urgency of recognizing and valuing women's work at the household level which has been systematically overlooked. At the same time, it has increased the demand for technology usage, exposing the gender digital divide. This article aims to shed light on the additional burden women are facing, especially when trying to balance unpaid care work with paid employment from the seclusion of their homes. We do this by reviewing a number of surveys conducted in Indonesia. We combine this with other examples from additional contexts in order to draw attention to a global trend of amplified inequalities and struggles women are experiencing. We advocate for an urgent paradigm shift by providing vital recommendations for policymakers and managers.
Keywords: 2000 à aujourd'hui; 2020-2029; asie; covid-19; indonésie; pandémie; pauvreté; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travail non rémunéré; travail précaire; violences; violences domestiques; violences envers les femmes*